2018
DOI: 10.1007/s00345-018-2231-9
|View full text |Cite
|
Sign up to set email alerts
|

Is mini-percutaneous nephrolithotomy a safe alternative to extracorporeal shockwave lithotripsy in pediatric age group in borderline stones? a randomized prospective study

Abstract: According to Clavien grade of complications mini-PCNL is a safe procedure, and after three session of ESWL, mini-PCNL has a similar stone-free rate with a lower retreatment rate. However, the mini-PCNL has more radiation exposure, and requires a longer hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…Different studies were conducted in which they compared the SFR of mini-PCNL and ESWL for 1–2 cm stone in the pediatric population. The SFR after first session was 88.9% for PCNL and 55.6% for ESWL ( P = 0.006) ( 28 ). Another study was done in China on 46 infants in which they compared the SFR of mini-PCNL and ESWL in infants under three years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies were conducted in which they compared the SFR of mini-PCNL and ESWL for 1–2 cm stone in the pediatric population. The SFR after first session was 88.9% for PCNL and 55.6% for ESWL ( P = 0.006) ( 28 ). Another study was done in China on 46 infants in which they compared the SFR of mini-PCNL and ESWL in infants under three years of age.…”
Section: Discussionmentioning
confidence: 99%
“…We had early SFR about 90% and total SFR 95.3%, which was higher than other studies, and 5.3% residual stone fragment. Farouk et al ( 26 ) performed a prospective study on 108 pediatric patients with 1- to 2-cm renal stone and randomized them into two groups to compare MPCNL and ESWL. Those who underwent MPCNL had 88.9% SFR after the first session surgery and reached 92.59% SFR after the second-look PCNL.…”
Section: Discussionmentioning
confidence: 99%
“…Those who underwent MPCNL had 88.9% SFR after the first session surgery and reached 92.59% SFR after the second-look PCNL. However, the ESWL group had 55.6% after the first session and reached 88.89% SFR after the third session of ESWL ( 26 ). Another study compared the outcomes of super-MPCNL and retrograde intra-renal surgery (RIRS) for children with upper urinary tract calculus.…”
Section: Discussionmentioning
confidence: 99%
“…12,19 Even though, some studies reported a lower SFR. 20 The predictors of the stone-free rate after PCNL were studied in literature. To illustrate, Shahror, K, et al reported that the stone size, number, location, and pelvicalyceal system anatomy were significant predictors of SFR.…”
Section: Discussionmentioning
confidence: 99%